Cost Analysis Of Replacement And Bearing Trailer Maintenance In Sugar Group Companies - Mastur Mastur; Masyhuri Masyhuri; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
The purpose of this study are to understand (i) the costs and periods optimal of grease used for the replacement and maintenance bearing trailer in Sugar Group Companies (SGC), and (ii) the effect of a period and frequency of grease, lifetime bearing, frequency of replacement bearing in a year, unit trailer, brand bearing, and location of plant. The basic method used is descriptive and analytical. The location determined were in Workshop Division PT. ILP, PT. SIL, and PT. GPM. The analytical method used analytical tables, charts, and multiple regression analysis. The optimal period of grease based on bearing replacement and maintenance costs: (i) PT. ILP both brand A and B: Fertilizer Trailers (FT), Water Tank (WT), Side Tipping Trailer (STT), and Tank Moving (TS) is on 5 days, while Patria (PTR) and Disc Harrow (DH) on 3 days; (ii) PT. SIL both brand A and B unit trailer: FT, WT, PTR, STT, and TS on 5 days unless DH on 3 days; and (iii) PT. GPM for brands B for all unit (FT, WT, PTR, STT, TS, and DH) on 5 days, nor brand A except DH on 3 days. The factors that effect is a period of grease, bearing replacement and frequency of grease in one year. Cost of replacement and maintenance brand A < B. PT. ILP has the lowest costs than PT. SIL and PT. GPM.